Method for regulating and controlling ternary positive electrode material interface through solid polymer electrolyte

The surface of the ternary positive electrode material is covered and the lithium ion transmission channel is constructed through solid polymer electrolyte, which solves the safety hazards when the liquid electrolyte comes into contact with lithium metal in lithium-ion batteries and the problem of poor contact with the solid electrolyte interface, and achieves optimization of battery performance and improvement of safety.

CN119890236APending Publication Date: 2025-04-25QINGDAO YINGKE PRECISION RUBBER & PLASTIC CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510059323.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In commercial lithium-ion batteries, there are safety hazards when liquid electrolytes come into direct contact with lithium metal, such as the growth of lithium dendrites and the decomposition of electrolytes, which lead to deterioration of battery performance and combustion explosion. At the same time, the interface contact between the solid electrolyte and the electrode is poor, which limits the use of the solid electrolyte.

Method used

The solid polymer electrolyte is used to completely coat the surface of the ternary positive electrode material by selecting a stable polymer substrate to improve the contact between the positive electrode and the electrolyte, and build an efficient lithium ion transmission channel in the positive electrode.

Benefits of technology

It achieves good contact between the positive electrode and the electrolyte, reduces internal resistance and interface impedance, promotes the transmission of lithium ions, optimizes the battery's magnification and cycling performance, and improves the battery's safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005242382550000011
    Figure HDA0005242382550000011
  • Figure HDA0005242382550000012
    Figure HDA0005242382550000012
  • Figure HDA0005242382550000021
    Figure HDA0005242382550000021
Patent Text Reader

Abstract

The invention provides a method for regulating and controlling a ternary positive electrode material interface by using a solid polymer electrolyte, and belongs to the technical field of lithium ion battery materials, and the method comprises the following steps: 1) mixing and grinding a ternary active material, a binder, a conductive auxiliary agent and a first solvent to obtain positive electrode slurry; (2) preparing the positive electrode slurry obtained in the step (1) into a positive electrode plate; 3) mixing a polymer matrix and a second solvent to obtain a first solution; 4) adding a lithium salt into the first solution obtained in the step 3) to obtain a positive electrode modification solution; and (5) infiltrating the positive pole piece in the step (2) into the positive pole modification solution in the step (4), taking out, and drying to obtain the modified positive pole. According to the regulation and control method provided by the invention, while an electron transport network in the positive electrode material is reserved, the high-performance electrolyte is filled in the positive electrode, and an efficient ion transport channel is constructed in the positive electrode, so that the transmission of lithium ions is promoted, and the rate and cycle performance of the battery are optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery materials, and in particular relates to a method for regulating the interface of a ternary positive electrode material using a solid polymer electrolyte. Background Art

[0002] Lithium-ion batteries have been widely used in the consumer electronics and electric vehicle markets due to their high energy density, long cycle life, small memory effect, and low self-discharge capacity. However, commercial Li-ion batteries currently use liquid electrolytes based on carbonates or ethers, which pose a safety risk of being flammable and explosive. At the same time, commercial lithium batteries use graphite as the negative electrode, which greatly limits the improvement of lithium battery energy density. In order to adapt to market demand and development trends, it is necessary to improve energy density, and the use of lithium metal as the negative electrode is a promising direction. However, due to the strong reduction reaction activity of lithium metal, there are considerable problems and safety hazards when liquid-based electrolytes are in direct contact with it, such as the growth of lithium dendrites, the decomposition of the electrolyte, etc., which causes the performance degradation of the battery pack and even combustion and explosion.

[0003] The use of solid electrolytes to replace liquid electrolytes fundamentally improves the safety of batteries. However, the interface problem between solid electrolytes and electrodes greatly limits the application of solid electrolytes. Unlike the complete wetting of electrode materials by electrolytes, the contact between solid electrolytes and electrodes is limited to local "point-to-point" or "surface-to-surface" contact, so the interface contact is poor and the cathode material cannot be fully utilized. On the other hand, there is an instability problem between electrodes and electrolytes, especially nickel-rich cathode materials. For example, serious interfacial side reactions between nickel-rich ternary cathodes and sulfide solid electrolytes will lead to oxidative decomposition of sulfide solid electrolytes. The formation of unstable cathode / electrolyte interfaces and the degradation of the surface structure of nickel-rich cathodes will lead to low initial capacity and coulombic efficiency, as well as rapid capacity decay. Li et al. coated nanoscale lithium phosphide oxide (LiPON) on the surface of nickel-rich cathodes (NCM811), eliminating the side reactions at the electrode-electrolyte interface while maintaining the stability of the surface structure of active particles, achieving stable and long-lasting battery cycles (Energy Storage Materials, 2022, 45, 1165-1174). Wang et al. proposed a positive electrode supporting solid electrolyte membrane framework to improve the interface contact between the solid electrolyte and the electrode. The solid electrolyte was directly cast on the positive electrode layer to enhance the wetting ability of the solid electrolyte on the positive electrode and enhance the interface adhesion. The performance of the prepared solid-state battery was improved (Energy & Environmental Science, 2019, 12(3): 938-944).

[0004] These schemes focus on studying the interface problems between the cathode and the electrolyte, enhancing the wetting ability of the solid electrolyte to the cathode, improving the solid electrolyte interface contact, and surface treatment to eliminate side reactions. However, these methods often require expensive equipment and complex procedures to achieve a stable interface and high electrochemical performance. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a method for regulating the interface of ternary positive electrode materials by solid polymer electrolyte. The present invention selects a polymer substrate that is stable for high-nickel positive electrode, completely covers the surface of positive electrode active material, achieves good contact between positive electrode and electrolyte, and constructs efficient lithium ion transmission channel in positive electrode, promotes rapid transport of lithium ions, and optimizes battery rate and cycle performance.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for regulating the interface of a ternary positive electrode material by a solid polymer electrolyte, comprising the following steps:

[0008] 1) mixing and grinding the ternary active material, the binder, the conductive additive and the first solvent to obtain a positive electrode slurry;

[0009] 2) preparing a positive electrode sheet from the positive electrode slurry obtained in step 1);

[0010] 3) mixing the polymer matrix and the second solvent to obtain a first solution;

[0011] 4) adding lithium salt to the first solution obtained in step 3) to obtain a positive electrode modification solution;

[0012] 5) Immersing the positive electrode sheet described in step 2) in the positive electrode modification solution described in step 4), taking it out and drying it to obtain a modified positive electrode.

[0013] Preferably, the ternary active material is NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), NCM811(LiNi 0.8 Co 0.1 Mn 0.1 O2), NCA(LiNi 0.8 Co 0.15 Mn 0.05 O2) at least one.

[0014] Preferably, the first solvent comprises N-methylpyrrolidone.

[0015] Preferably, the polymer matrix includes at least one of polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride, polyethylene oxide and polyionic liquid.

[0016] Preferably, the second solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide and acetonitrile.

[0017] Preferably, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium nitrate.

[0018] Preferably, the mass ratio of the second solvent to the polymer matrix is ​​6:1 to 10:1.

[0019] Preferably, the mass ratio of the polymer matrix to the lithium salt is 1:1 to 1:4.

[0020] The present invention also provides a positive electrode material obtained by regulating the above method.

[0021] The present invention also provides the use of the positive electrode material in preparing a positive electrode of a lithium ion battery.

[0022] The present invention has the following beneficial effects:

[0023] 1. The method for regulating the interface of the ternary material provided by the present invention selects PVDF-HFP as the polymer substrate to achieve surface coating of the ternary active material, improve the rigid contact between the positive electrode and the electrolyte, reduce the internal resistance and interface impedance, and stabilize the interface contact between the high nickel material and the electrolyte material.

[0024] 2. The method for regulating the interface of the ternary material provided by the present invention, while retaining the electron transport network in the positive electrode material, constructs an efficient ion transport channel in the positive electrode by filling the positive electrode with a high-performance electrolyte, thereby promoting the transmission of lithium ions and optimizing the battery's rate and cycle performance.

[0025] 3. The processing method adopted by the present invention is simple to prepare, and the materials used are common and easy to purchase, and can be applied to mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 0.2C cycle performance diagram of polymer solid-state batteries obtained in Example 1, Example 2 and Comparative Example 1;

[0027] Figure 2 The figure is a rate performance diagram of the polymer solid-state battery obtained in Example 1, Example 2 and Comparative Example 1;

[0028] Figure 3 The graph is a test result of the interface impedance of the polymer solid-state battery obtained in Example 1, Example 2 and Comparative Example 1;

[0029] Figure 4 This is a cross-sectional morphology of the positive electrode after regulation obtained in Example 1. DETAILED DESCRIPTION

[0030] The present invention provides a method for regulating the interface of a ternary positive electrode material by a solid polymer electrolyte, comprising the following steps:

[0031] 1) mixing and grinding the ternary active material, the binder, the conductive additive and the first solvent to obtain a positive electrode slurry;

[0032] 2) preparing a positive electrode sheet from the positive electrode slurry obtained in step 1);

[0033] 3) mixing the polymer matrix and the second solvent to obtain a first solution;

[0034] 4) adding lithium salt to the first solution obtained in step 3) to obtain a positive electrode modification solution;

[0035] 5) Immersing the positive electrode sheet described in step 2) in the positive electrode modification solution described in step 4), taking it out and drying it to obtain a modified positive electrode.

[0036] The present invention has no special limitation on the sources of the ternary active material, the binder and the conductive additive, and conventional commercial products in the art may be used.

[0037] In the present invention, the ternary active material is preferably NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), NCM811(LiNi 0.8 Co 0.1 Mn 0.1 O2), NCA(LiNi 0.8 Co 0.15 Mn 0.05 O2) at least one.

[0038] In the present invention, the binder is preferably polyvinylidene fluoride (PVDF), the conductive additive is preferably conductive carbon black (SuperP), and the first solvent is preferably N-methylpyrrolidone (NMP).

[0039] In the present invention, the method for preparing the positive electrode slurry into a positive electrode sheet is preferably to apply the positive electrode slurry to a certain thickness on an aluminum foil, dry it in a vacuum oven to obtain a positive electrode material, and punch it to obtain a positive electrode sheet.

[0040] In the present invention, the coating thickness is preferably 50 to 100 μm.

[0041] In the present invention, the drying method is preferably to place the mixture at 60° C. for 1 hour and then at 120° C. for 12 hours.

[0042] In the present invention, the polymer matrix preferably includes at least one of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), and polyionic liquid.

[0043] In the present invention, the second solvent preferably includes at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and acetonitrile (ACN).

[0044] In the present invention, the mass ratio of the second solvent to the polymer matrix is ​​preferably 6:1 to 10:1.

[0045] In the present invention, the lithium salt preferably includes at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium nitrate (LiNO 3 ).

[0046] In the present invention, the mass ratio of the polymer matrix to the lithium salt is preferably 1:1 to 1:4.

[0047] In the present invention, the positive electrode sheet is preferably immersed in the positive electrode modification solution for 0.5 to 12 hours; after being taken out, the drying temperature is preferably 50 to 100° C., and the drying time is preferably 4 to 12 hours.

[0048] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0049] Example 1

[0050] NCM622, PVDF, and SuperP were mixed in a ratio of 8:1:1, and NMP was added to grind to obtain a positive electrode slurry; the positive electrode slurry was scraped on an aluminum foil with a diameter of 75 μm, placed in a vacuum oven at 60°C for 1 hour, and then placed at 120 degrees for 12 hours to obtain the required electrode; 500 mg PVDF-HFP was dispersed in 4.5 g NMP, and after uniform dispersion, 1 g LiTFSI was added thereto, and magnetic stirring was performed for 24 hours to obtain a uniform and stable positive electrode modification solution; the electrode was immersed in the modification solution for 0.5 hours, and then placed in a vacuum drying oven at 60°C for 10 hours to obtain a regulated positive electrode.

[0051] Example 2

[0052] NCM622, PVDF, and SuperP were mixed in a ratio of 8:1:1, and NMP was added to grind to obtain a positive electrode slurry; the positive electrode slurry was scraped on an aluminum foil with a diameter of 75 μm, placed in a vacuum oven at 60°C for 1 hour, and then placed at 120 degrees for 12 hours to obtain the required electrode piece; 500 mg PVDF-HFP was dispersed in 4.5 g NMP, and after uniform dispersion, 1 g LiTFSI was added thereto, and magnetic stirring was performed for 24 hours to obtain a uniform and stable positive electrode modification solution; the electrode piece was immersed in the modification solution for 10 hours, and then placed in a vacuum drying oven at 60°C for 10 hours to obtain a regulated positive electrode.

[0053] Comparative Example 1

[0054] Compared with the embodiment, the main difference is that the positive electrode is not modified, specifically:

[0055] NCM622, PVDF, and SuperP were mixed in a ratio of 8:1:1, and NMP was added to grind to obtain a positive electrode slurry; the positive electrode slurry was scraped on an aluminum foil at 75 μm, placed in a vacuum oven at 60°C for 1 hour, and then placed at 120 degrees for 12 hours to obtain the required electrode; 500 mg PVDF-HFP was dispersed in 4.5 g NMP, and after uniform dispersion, 1 g LiTFSI was added thereto, and magnetic stirring was performed for 24 hours to obtain a uniform and stable polymer electrolyte solution; the electrolyte solution was coated on a polyimide film with a scraper, and then placed in a vacuum drying oven at 60°C for 12 hours to obtain a polymer electrolyte membrane with a thickness of 40-100 μm.

[0056] Electrochemical tests were performed on the electrodes prepared in Examples 1-2 and Comparative Example 1 and the polymer electrolyte.

[0057] Research has found that when the positive electrode is not surface treated, the poor interface contact between the positive electrode and the polymer electrolyte increases polarization, hinders the transmission of lithium ions at the interface, and leads to poor electrochemical performance of the battery. After the positive electrode is surface treated, the interface contact between the positive electrode and the electrolyte is improved, the internal resistance and interface impedance are reduced, and the transmission of lithium ions is promoted, thereby obtaining better rate and cycle performance.

[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for regulating the interface of a ternary cathode material using a solid polymer electrolyte, characterized in that: The following steps are involved: 1) mixing and grinding the ternary active material, the binder, the conductive additive and the first solvent to obtain a positive electrode slurry; 2) preparing a positive electrode sheet from the positive electrode slurry obtained in step 1); 3) mixing the polymer matrix and the second solvent to obtain a first solution; 4) adding lithium salt to the first solution obtained in step 3) to obtain a positive electrode modification solution; 5) Immersing the positive electrode sheet described in step 2) in the positive electrode modification solution described in step 4), taking it out and drying it to obtain a modified positive electrode.

2. The method for regulating the interface of a ternary cathode material using a solid polymer electrolyte according to claim 1, characterized in that: In step 1), the ternary active material is NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), NCM811(LiNi 0.8 Co 0.1 Mn 0.1 O2), NCA(LiNi 0.8 Co 0.15 Mn 0.05 O2) at least one.

3. The method for regulating the interface of ternary cathode materials by a solid polymer electrolyte according to claim 1, characterized in that: The first solvent includes N-methylpyrrolidone.

4. The method for regulating the interface of a ternary cathode material by a solid polymer electrolyte according to claim 1, characterized in that: In the step 3), the polymer matrix includes at least one of polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride, polyethylene oxide and polyionic liquid.

5. The method for regulating the interface of ternary cathode materials by using a solid polymer electrolyte according to claim 1, characterized in that: The second solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide and acetonitrile.

6. The method for regulating the interface of ternary cathode materials by using a solid polymer electrolyte according to claim 1, characterized in that: The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium nitrate.

7. The method for regulating the interface of ternary cathode materials by using a solid polymer electrolyte according to claim 1, characterized in that: In the step 3), the mass ratio of the second solvent to the polymer matrix is ​​6:1 to 10:

1.

8. The method for regulating the interface of ternary cathode materials by using a solid polymer electrolyte according to claim 1, characterized in that: The mass ratio of the polymer matrix to the lithium salt is 1:1 to 1:

4.

9. A positive electrode material obtained by controlling the interface of a ternary positive electrode material using a solid polymer electrolyte as claimed in any one of claims 1 to 8.

10. Use of the positive electrode material according to claim 9 in preparing a positive electrode for a lithium ion battery.

Citation Information

Patent Citations

  • Solid-state electrolyte positive pole and solid-state battery containing same

    CN109004265A

  • A composite cathode for a solid-state battery and a preparation method thereof

    CN109119591A

  • Solid-state lithium battery and preparation method thereof

    CN112421103A

  • Lithium metal solid-state battery capable of operating at room temperature and preparation method of lithium metal solid-state battery

    CN114665150A

  • Composite positive pole piece, preparation method thereof and lithium battery

    CN116053401A